Potential of Green Gram Flour as an Enrobing Material for Papaya-Pulp Enriched Chicken Nuggets - Para, Parveez Ahmad; Kumar, Sunil; Raja, Waseem Hussain; Bhat, Z.F.; Kumar, Arvind (Journal of Meat Science, 2015)
A study was conducted to evaluate the possibility of utilization of green gram flour (GGF) as an enrobing material for papaya pulp-enriched chicken nuggets. GGF was used at two different levels in the batter mix viz. 25 % (w/w) and 35 % (w/w) separately and analyzed for various quality parameters. The products developed were assessed for various physicochemical, proximate and sensory parameters. A significant effect (p< 0.05) was observed on cooking yield, moisture percent, ether extract, ash content and crude fiber content of the products. Significantly (p 0.05) change was observed in colour and appearance, juiciness and flavour, however, a significant (p< 0.05) decrease was noted in the scores of texture and overall acceptability with increase in the level of green gram flour in the batter mix. Based on various quality parameters, 25 % level of GGF was optimized as best for enrobing of papaya pulp-enriched chicken nuggets.
Keywords: Chicken sausages; Emulsion pH; Hurdle technology; Textured soya protein